Equipment and procedures for triaxial testing of subgrade soils - Hormych, P. (1996)
One of the aims of the laboratory twinning project “A European Approach to Road Pavement Design” was to develop standard test procedures for repeated load triaxial testing of subgrade soils. For this purpose, repeatability tests were carried out to compare the triaxial equipment and test procedures of the four participating laboratories. This paper presents the results of these tests, and concludes by some recommendations for cyclic triaxial testing of subgrade soils.